Modelling and dynamic simulation of a parabolic trough power plant. (March 2016) - Al-Maliki, Wisam Abed Kattea; Alobaid, Falah; Kez, Vitali; Epple, Bernd
Highlights: A detailed dynamic model of a parabolic trough power plant is presented. Solar field, thermal storage, power block and all automation processes are modelled. APROS model can quantitatively represents real power plant at different summer days. Simulated results are compared to measured data from an existing solar power plant. The comparison shows an excellent agreement. Abstract: Investigational dynamic simulations of an existing 50 MWel parabolic trough solar thermal power plant in Spain are carried out during clear days and slightly cloudy periods. This work is the first research, which presents a detail dynamic model of a parabolic trough power plant. Besides the thermal energy storage system and solar field, the developed model describes the heat transfer fluid and steam/water paths in detail. Advanced control circuits, including drum level, economiser water bypass, attemperator and steam bypass controllers are also included. The parabolic trough power plant is modelled using Advanced Process Simulation Software (APROS). The comparison between the simulation results and measured data is documented, showing a reliable prediction of the real behaviour of the investigated solar power plant. The validated model offers a possibility for accurate simulation of further operation processes of the real plant.